Persistent candida arthritis successfully treated with micafungin instillation and surgery. A case report - Jeroen C. van Egmond; Nicole G.M. Hunfeld; Bart J.A. Rijnders; Jan A.N. Verhaar (Medical Mycology Case Reports, 2020)
We report a rare case of C. krusei knee arthritis treated with instillation of micafungin and arthroscopy. A 49-year-old man hospitalized for treatment of Acute Myeloid Leukemia developed knee arthritis with C. krusei. He was treated with a combination of arthroscopic debridement, intravenous as well as intra-articular micafungin. Serum and intra-articular concentrations of micafungin were determined. After instillation of micafungin in the knee and arthroscopic debridement, the patient completely recovered. Keywords: Candida, Micafungin, Knee, Arthritis, Instillation